Immune alterations, lipid peroxidation, and muscle damage following a hill race - Simpson, R. J.; Wilson, M. R.; Black, J. R.; Ross, J. A.; Whyte, G. P.; Guy, K.; Florida-James, G. D. (Canadian Journal of Applied Physiology, 2005)
Hill races usually include large downhill running sections, which can induce significant degrees of muscle damage in a field setting. This study examined the link between muscle damage, oxidative stress, and immune perturbations following a 7-km mountainous hill race with 457 m of ascent and 457 m of descent. Venous blood samples were taken from 7 club level runners before, immediately after, and 48 hrs postrace. Samples were analysed for total and differential leukocyte counts, markers of muscle damage (CK), lipid peroxidation (MDA), and acute phase proteins (CRP; fibrinogen; a-1-ACT). The total antioxidant status (TEAC) and plasma levels of the proinflammatory cytokines IL-6, IL-8, and TNF-a were also determined. Subjective pain reports, and plasma activities of CK, MDA, and circulatory monocytes reached peak values at 48 hrs postrace (p < 0.05). TEAC and the cytokine IL-8 increased immediately after the race (p < 0.05). Plasma TNF-a remained unchanged (p > 0.05). Despite the reports of muscle damage and soreness, no evidence of an acute phase response was observed (p > 0.05), which may be explained by the failure of the race to induce a plasma TNF-a response. Future studies should examine the link between muscle damage, oxidative stress, and the acute phase response following hill races of longer duration with larger eccentric components.